Development of vertical movement stabilizer for vehicle active suspension system - Alireza, Rezanoori (2019)
An advanced suspension system recommends more handling, safety, comfortable ride and fast reaction. Such a system is capable to scan changing of road profile and its conditions and also monitor factors such as car speed and steering wheel angle. Application of different sensors such as laser sensor or stereo camera for scanning road profile and different types of mechanical mechanism such as hydro pneumatic or hydraulic system for readjusting axles are challenges between car manufacturers. In this research, a new method is proposed for improving the vertical movement mechanism in suspension system of vehicles. The proposed method is based on vertical movement mechanism which is equipped with a monitoring system to scan the road profile for stabilizing car chassis. This system will analyze steering wheel angle, weather conditions, the distance between cars during accident and car speed in order to adjust the height of the car’s axles accordingly. Such mechanism can increase comfortability, car handling stability and safety by reducing the vertical movements. Besides that, the proposed system will increase the safety of the passengers by reducing vertical movements that may cause car’s imbalance or rollover during driving. A prototype of a vertical movement model was developed to simulate its function during different driving profiles and conditions. The purpose of the simulation based on the half-car model is to utilize the function performance of the device in a laboratory scale. It is worth to note that the proposed method successfully reduces the vertical movement up to 33% compared to normal suspension system. While the model reduces the impact during an accident of 44% for contact between car bumpers. In summary the system successfully adjusts the height of axles according to car speed, weather condition and steering wheel angle to prevent of rollover of the car. This system can be used in the automotive industry for passenger cars and light trucks. Furthermore, with some modifications, this system can be applied in mass transit, aerospace industry and marine transportation.